(untitled) (Revista Logos Ciencia & Tecnología, 2018)
The present study sought to analyse the behavioural attitudes that are generated in the free time of students mainly in the time of rest as an influential element in the development of prosocial skills, which contributes to improving the interpersonal relations of coexistence of girls and boys of Fe y Alegría schools and propose activities that allow to improve the healthy coexistence. The study has its paradigmatic basis in positivism, with a non-experimental design. Responds to a type of field research, descriptive level, with a quantitative approach to collect information based on the inquiry of three dimensions: a) prosocial skills; b) management strategies / activities; and c) social and emotional behaviour. The population was constituted by 120 teachers and 1000 students. A questionnaire of scale type Lickert was applied, each instrument (teachers and students) consists of 37 items whose reliability was 0.8 and Kappa index 0.7. Results show that prosocial competences, managerial strategies and the characteristics of teachers and students have a direct relationship in the behaviour of students when assuming a peaceful attitude for the solution of conflicts.